Madrasah Principal's Strategy in Improving Teacher's Digitalisation Skills at Mis Al-Iqro Belawan Medan - Daulay, Isma Hayati; Mesiono; Nasution, Inom (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyse the madrasah head's strategy in improving teachers' digitalisation skills. This research is motivated by the importance of digitalisation in teachers in supporting the future development of the nation and developing the potential of teachers in facing global competition. The type of research used in this study is qualitative. Data sources were obtained from MIS Al-Iqro' Belawan Medan through observation, interviews and documents. The results obtained in the study of the madrasah head's strategy in improving the digitalisation skills of teachers at MIS Al-Iqro' Belawan Medan are: (1) Teachers' digitalisation skills at MIS Al-Iqro' Belawan Medan vary, but generally show significant improvement after attending training programmes and workshops provided by the madrasah, (2) Implementation of strategies carried out by madrasah principals includes various training programmes, workshops, and seminars that focus on improving teachers' digital skills, (3) Evaluation of the implemented strategies shows positive results, with increased skills and confidence of teachers in using digital technology. Evaluation is conducted through classroom observations, skills tests, and feedback from teachers.